Eka Kustha (Psoriasis)- A Comprehensive Review of Ayurvedic and Modern Approaches (AYUSHDHARA, 2025)
Psoriasis, known as Eka Kustha in Ayurveda, is a chronic inflammatory skin condition that arises from immune system dysfunction, characterized by red, scaly patches. This disorder significantly affects the quality of life of those diagnosed. Psoriasis is considered a multifactorial disease, affected by a combination of genetic predispositions, environmental triggers, and immune system factors. This review seeks to explore psoriasis comprehensively through both Ayurvedic and contemporary medical lenses, focusing on its underlying mechanisms, treatment options, and the effectiveness of various approaches. From an Ayurvedic viewpoint, Eka Kustha stems from an imbalance in the Tridosha system, which can be exacerbated by poor dietary choices and lifestyle habits. This imbalance leads to toxin build-up and diminishes proper immune function. Ayurvedic treatments emphasize detoxification methods such as Panchakarma, the use of herbal medicines, and dietary adjustments to restore balance among the Doshas and enhance overall wellness. Conversely, modern medicine approaches psoriasis as an autoimmune condition that entails an imbalance in T cell activity and cytokines, including TNF-α, IL-17, and IL-23. Treatment in conventional medicine encompasses a range of options from topical corticosteroids and systemic immunosuppressants to advanced therapies like biologics and phototherapy, aimed at alleviating symptoms and managing the disease. Nonetheless, these methods may present adverse effects and typically necessitate ongoing treatment. A comparative assessment of these two frameworks reveals that while modern medical interventions can provide swift symptom relief, Ayurvedic practices may deliver long-term advantages by tackling the fundamental causes of the disease and fostering immune balance. The potential integration of Ayurvedic detoxification techniques and herbal solutions with modern therapeutic advancements holds promise for enhancing patient outcomes. Further clinical investigations are necessary to develop evidence-based integrative treatment protocols for psoriasis, aiming for a comprehensive and sustainable approach to managing this condition.